A Wadi Suq Necropolis in The Mountains Rescue Excavations at Bilad Ash Shuhum (Adh-Dhahira, Oman) - Gernez, Guillaume; al-Ghafri, Waleed; Ciesielski, Elsa (The Journal of Oman Studies, 2025)
Rescue excavations carried out at Bilad Sahum (adh-Dhahira) have identified a necropolis of the Middle Bronze Age (Wadi Suq period). The architectural characteristics of the 9 excavated subterranean cist graves, and the homogeneity of the archaeological material, especially the soft-stone vessels, suggest that the necropolis was used for a relatively short period, and - quite rarely - no evidence of later reuse was observed, although most of them had been looted. This is the first Middle Bronze Age necropolis discovered in the mid-mountain region, at an altitude of nearly 1000 m above sea level, which attests to the occupation of this environment at the beginning of the 2nd millennium BCE.